A new species of Gynacantha Rambur, 1842 from Cat Tien National Park, Vietnam (Odonata: Aeshnidae) - Kompier, Tom; Holden, James (Zootaxa, 2017)
Gynacantha cattienensis spec. nov. is described from Cat Tien National Park, Dong Nai Province, Vietnam, on the basis of male and female specimens. This species is close in structure to G. khasiaca McLachlan, 1896, and differs in details of cerci, auricles and thorax coloration. Historical records of G. khasiaca from Vietnam may refer to this new species. Some information on its biology is provided.